2021
DOI: 10.3390/s21217067
|View full text |Cite
|
Sign up to set email alerts
|

Refining Atmosphere Profiles for Aerial Target Detection Models

Abstract: Atmospheric path radiance in the infrared is an extremely important quantity in calculating system performance in certain infrared detection systems. For infrared search and track (IRST) system performance calculations, the path radiance competes with the target for precious detector well electrons. In addition, the radiance differential between the target and the path radiance defines the signal level that must be detected. Long-range, high-performance, offensive IRST system design depends on accurate path ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…It has been shown that for a clear sky background, moderate resolution atmospheric transmission (MODTRAN) is an accurate atmospheric model for predicting background path radiance in the LWIR and MWIR. 17 Using either radiosonde historic averages or importing exact day radiosonde data from a specific location, 18 the measured and MODTRAN modeled background path radiance produces similar results. The error in the SNR or signal-to-clutter ration is much lower when importing radiosonde data into MODTRAN rather than using standard atmosphere models.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…It has been shown that for a clear sky background, moderate resolution atmospheric transmission (MODTRAN) is an accurate atmospheric model for predicting background path radiance in the LWIR and MWIR. 17 Using either radiosonde historic averages or importing exact day radiosonde data from a specific location, 18 the measured and MODTRAN modeled background path radiance produces similar results. The error in the SNR or signal-to-clutter ration is much lower when importing radiosonde data into MODTRAN rather than using standard atmosphere models.…”
Section: Introductionmentioning
confidence: 93%
“…Radiosonde data can be used to more closely match the path radiance of any atmosphere and that work inspired using the same concept for cloud BBEQ temperatures. 17 Similar to the approach with the clear skies, nighttime cloud data are taken near the time of a radiosonde sounding 18 so the atmospheric data matched in time. The cloud modeling was done in the MODTRAN GUI version 6.1.2.…”
Section: Modtran Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…When the sky is not in view, the sky radiance can be quickly and accurately estimated using a radiation transfer software package, such as MODTRAN with local atmospheric conditions and radiosonde data. 13 In scenes where the sky is visible from horizon to zenith, the total path radiance incident on a surface can be determined. However, in most cases, only a portion of the sky is visible within the sensor's field of view (FOV).…”
Section: Estimating Sky Radiancementioning
confidence: 99%
“…In [ 5 ], continuing with aerial targets, we now proceed from RF to infrared (IR) imaging target acquisition. Atmospheric path radiance in infrared is extremely important in calculating system performance in certain infrared detection systems.…”
Section: Brief On Research Articles Publishedmentioning
confidence: 99%